1991
DOI: 10.1111/j.1365-3024.1991.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of immunoglobulin and complement in enhancing the respiratory burst of neutrophils against Trichomonas vaginalis

Abstract: Human neutrophils, alone, did not kill Trichomonas vaginalis. More than 90% of T. vaginalis (10(5)/ml) survived in the presence of 10% normal human serum (NHS) while 90% of these organisms were killed in the presence of a combination of neutrophils (10(6)/ml) and 10% NHS. Mechanisms responsible for this serum-mediated neutrophil killing of T. vaginalis were demonstrated through a process of lucigenin-amplified neutrophil chemiluminescence. As evidenced by indirect immunofluorescence, NHS showed specific immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…Specific local antibodies, both IgG and IgA, have been identified in women only (Ackers et al 1975 andAlderete et al 1991a, b). It has been suggested that natural antibodies to the parasite, generated by cross-reacting antigens with the normal vaginal flora, may enhance the complement-mediated lysis (Shaio et al 1991). Specific antibody responses to T. vaginalis antigens in serum have also been reported (Alderete et al 1991c); however, similar to their local counterparts, these circulating antibody levels also differ and appear to have no function in helping the host to get rid of the infection (Honigberg 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Specific local antibodies, both IgG and IgA, have been identified in women only (Ackers et al 1975 andAlderete et al 1991a, b). It has been suggested that natural antibodies to the parasite, generated by cross-reacting antigens with the normal vaginal flora, may enhance the complement-mediated lysis (Shaio et al 1991). Specific antibody responses to T. vaginalis antigens in serum have also been reported (Alderete et al 1991c); however, similar to their local counterparts, these circulating antibody levels also differ and appear to have no function in helping the host to get rid of the infection (Honigberg 1990).…”
Section: Discussionmentioning
confidence: 99%
“…The innate, local, nonspecific defense mechanisms against T. vaginalis include activation of alternative pathway of the complement system, induction of toll‐like receptors (TLRs) and abundant accumulation of polymorphonuclear neutrophils and macrophages . The pathogen is susceptible to direct complement‐mediated killing, and complement activation provides C3 opsonin that promotes neutrophil‐mediated phagocytosis of T. vaginalis but high iron‐induced cysteine proteases protect the parasite from complement‐related lysis . It has also been reported that T. vaginalis can acquire host CD59 from various cells, such as RBCs, which may be another complement evasion strategy …”
Section: Innate Immunity During T Vaginalis Infectionmentioning
confidence: 99%
“…Recent evidence indicates that C3 can play a role in the recruitment of granulocytes during inflammation (29,51,52), as neutrophil infiltration is markedly reduced in C3-deficient mice. In addition, C3 is involved in the IgG-dependent and -independent induction of the respiratory burst in neutrophils (53)(54)(55)(56). Furthermore, complement facilitates killing of the parasitic protozoan Trichomonas vaginalis by neutrophils by enhancing the respiratory burst (53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, C3 is involved in the IgG-dependent and -independent induction of the respiratory burst in neutrophils (53)(54)(55)(56). Furthermore, complement facilitates killing of the parasitic protozoan Trichomonas vaginalis by neutrophils by enhancing the respiratory burst (53). A defect or delay in granulocyte recruitment or impairment of the respiratory burst could explain the ineffectiveness of PZQ treatment in C3-deficient mice.…”
Section: Discussionmentioning
confidence: 99%